Small molecule-mediated stabilization of vesicle-associated helical Alpha-synuclein inhibits patogenic misfolding and aggregation - Fonseca Ornelas, Luis (2014)
α-synuclein is an abundant presynaptic protein that is important for regulation of synaptic vesicle trafficking, and whose misfolding plays a key role in Parkinson’s disease. While α-synuclein is disordered in solution, it folds into a helical conformation when bound to synaptic vesicles. Stabilization of helical, folded α-synuclein might therefore interfere with α-synuclein-induced neurotoxicity. Here we show that several small molecules, which delay aggregation of α-synuclein in solution, including the Parkinson’s disease drug selegiline, fail to interfere with misfolding of vesicle-bound α-synuclein. In contrast, the porphyrin phtalocyanine tetrasulfonate directly binds to vesicle-bound α-synuclein, stabilizes its helical conformation and thereby delays pathogenic misfolding and aggregation. Our study suggests that small-molecule-mediated stabilization of helical vesicle-bound α-synuclein opens new possibilities to target Parkinson’s disease and related synucleinopathies